ANTIARRHYTHMIC EFFICACY OF PROPAFENONE IN PATIENTS WITH PERSISTENT ATRIAL FIBRILLATION - R. D. Kurbanov; N. U. Zakirov; Sh. K. Azizov (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To assess propafenone antiarrhythmic efficacy and optimal timing of the drug administration for relief of persistent atrial fibrillation (PAF). Material and methods. 24 patients (19 men, 5 women, aged 53,8±13,3) with PAF (duration is more than 7 days) were included in the study. PAF was confirmed clinically as well as by ECG and daily ECG monitoring. Indications for sinus rhythm recovery by propafenone were defined in according to the ACC/AHA/ESC recommendations (2006). 12-lead ECG was performed before the fist administration and 2, 4, 8, 12, 24 hours and some next days after propafenone therapy start. Echocardiography and thyroid hormone tests were also performed. Propafenone was administered additionally to standard treatment of the underlying disease and oral anticoagulants. The first dose of propafenone was 300 mg, after 4 hours patients received next dose of 300 mg if atrial fibrillation persisted and no side effects were observed, then doses of 300 mg were administered every 6-8 hours (but not more than 900-1200 mg per day) during 5 days. Maintenance propafenone dose of 450-600 mg daily was used in case of sinus rhythm recovery. Results. Sinus rhythm was restored in 41,6% of patients taking propafenone, and time of sinus rhythm recovery was 53,1±28,9 hours after therapy start. Propafenone antiarrhythmic efficacy in the loading dose (300 mg) was 4,2%. Propafenone efficacy during the first 24 hours (dose of 700±282,8 mg) was 12,5%. The maximum rate of sinus rhythm recovery was observed during the first 2-3 days of propafenone receiving (60% of all patients with rhythm recovery). Patients with unrecovered sinus rhythm had longer duration of PAF in comparison with this in effectively treated patients, 105,8±89,0 vs 39,7±38,9 days (p<0,05), respectively, as well as the more prominent basal pulse deficit, 24,6±15,0 vs 13,56±5,7 beats per minute (p<0,05), respectively. Cardiac and transient noncardiac side effects were registered in 8,6 and 4,3% of patients taking propafenone in dose of 900-1200 mg/day, respectively. Side effects did not require propafenone therapy cessation. Conclusion. Propafenone (900-1200 mg/day) antiarrhythmic efficacy in PAF was 41,6%. The probability of sinus rhythm recovery was maximal during the first 2-3 days. Ineffectively treated patients had longer duration of PAF last episode and more prominent basal pulse deficit in comparison with these in effectively treated patients. Transient side effects not requiring propafenone (900-1200 mg/day) withdrawal were observed in 12,6% of patients.